An ever-looser union? Juxtaposing accumulation and agglomeration in the context of surveillance capitalism - Sonja Kleinod; Ulrich Klüh (Hochschule Darmstadt, Fachbereich Wirtschaft, Zentrum für Nachhaltige Wirtschafts- und Unternehmenspolitik ZNWU, 2020)
The article explores regional policy issues at the nexus of economic geography and the recent academic literature on the political economy of digitalization. The objective is to blend these two areas of research to derive a first set of preliminary policy implications for so called "Smart Region" strategies. First, we document and analyze the finding that digitalization and, more generally, technological progress based on information and communication technologies represents a risk rather than an opportunity for many regions. Against the backdrop of the role of human capital accumulation in this process, "Smart Region" strategies should re-focus their attention on the settlement and development of "digitally competent" human capital. Second, we summarize key findings from studies that deal with the capitalist accumulation regime emerging in the course of digital change. This regime, often referred to as "platform capitalism" or "surveillance capitalism", appears to be antagonistic what is considered an integral and functional regional economy. Against this background, regions should meet calls for a rapid integration into this regime with a good deal of skepticism. Similarly, they should be careful not to embrace "smart" initiatives overhasty. Instead, they should develop their own definition of digital literacy and consciously incorporate alternatives to platform capitalism in their digital strategies. Attracting digitally competent human capital can support such an approach, especially if the respective initiatives are directed towards the public, educational and non-profit sectors. – – Der Artikel untersucht regionalpolitische Fragen an der Schnittstelle von Wirtschaftsgeographie und neuerer wissenschaftlicher Literatur zur politischen Ökonomie der Digitalisierung. Ziel ist es, diese beiden Forschungsbereiche miteinander zu verbinden, um eine erste Reihe vorläufiger politischer Implikationen für so genannte "Smart Region"-Strategien abzuleiten. Zunächst dokumentieren und analysieren wir die Feststellung, dass die Digitalisierung und ganz allgemein der technologische Fortschritt auf der Grundlage der Informations- und Kommunikationstechnologien für viele Regionen eher ein Risiko als eine Chance darstellt. Vor dem Hintergrund der Rolle der Akkumulation von Humankapital in diesem Prozess sollten "Smart Region"-Strategien ihre Aufmerksamkeit wieder auf die Ansiedlung und Entwicklung von "digital kompetentem" Humankapital richten. Zweitens fassen wir zentrale Ergebnisse von Studien zusammen, die sich mit dem kapitalistischen Akkumulationsregime befassen, das im Zuge des digitalen Wandels entsteht. Dieses Regime, das oft als "Plattformkapitalismus" oder "Überwachungskapitalismus" bezeichnet wird, scheint dem entgegenzustehen, was als eine integrale und funktionale regionale Wirtschaft angesehen wird. Vor diesem Hintergrund sollten die Regionen Forderungen nach einer raschen Integration in dieses Regime mit viel Skepsis begegnen. Ebenso sollten sie sich davor hüten, "kluge" Initiativen voreilig zu ergreifen. Stattdessen sollten sie ihre eigene Definition von digitaler Kompetenz entwickeln und bewusst Alternativen zum Plattformkapitalismus in ihre digitalen Strategien einbeziehen. Die Gewinnung von digital kompetentem Humankapital kann einen solchen Ansatz unterstützen, insbesondere wenn die jeweiligen Initiativen auf den öffentlichen, den Bildungs- und den gemeinnützigen Sektor ausgerichtet sind.
Keywords: H4; J24; J45; J48; J61; L16; O3; P1; R1; R58; 330; Digitalization; Surveillance Capitalism; Platform Economy; Labour Markets; Regional Development; Smart Cities; Smart Regions; Economic Geography; Agglomeration; Human Capital